2019
DOI: 10.15420/ecr.2019.9.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Statins on the Functionality of CD4+CD25+FOXP3+ Regulatory T-cells in Acute Coronary Syndrome: A Systematic Review and Meta-analysis of Randomised Controlled Trials in Asian Populations

Abstract: Acute coronary syndrome (ACS) is characterised by increased effector cells and decreased regulatory T-cells (Tregs). Statins have been shown to be clinically beneficial in ACS patients. This effect could be mediated via the induction of Tregs in ACS patients. The aim of this systemic review and meta-analysis was to evaluate whether statin therapy enhances the frequency of Tregs determined by CD4+CD25+FOXP3+ in this subset of patients. A comprehensive search of PubMed and Embase was performed. Studies were rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…74 Studies in Asia recently reported that acute coronary syndrome is characterized by increased effector cells and decreased Tregs and that statins increase the frequency of CD4 þ CD25 þ T cells, although FOXP3 expression was not examined. 75 In a setting of acute myocardial infarction, patients were evaluated and found that atorvastatin treatment (80 mg) resulted in increased Treg frequency in peripheral blood and infarct-related coronary arteries accompanied by higher FOXP3 and TGF-b (TGFB) mRNA levels compared with the control group. 21 Moreover, in a retrospective study, patients with hypercholesterolemia treated with simvastatin (20 mg) or pravastatin (10 to 40 mg) for 4 or 8 weeks, respectively, exhibited increased frequency of CD4 þ CD25 high cells with upregulation of FOXP3 expression in the peripheral blood.…”
Section: Statinsmentioning
confidence: 99%
“…74 Studies in Asia recently reported that acute coronary syndrome is characterized by increased effector cells and decreased Tregs and that statins increase the frequency of CD4 þ CD25 þ T cells, although FOXP3 expression was not examined. 75 In a setting of acute myocardial infarction, patients were evaluated and found that atorvastatin treatment (80 mg) resulted in increased Treg frequency in peripheral blood and infarct-related coronary arteries accompanied by higher FOXP3 and TGF-b (TGFB) mRNA levels compared with the control group. 21 Moreover, in a retrospective study, patients with hypercholesterolemia treated with simvastatin (20 mg) or pravastatin (10 to 40 mg) for 4 or 8 weeks, respectively, exhibited increased frequency of CD4 þ CD25 high cells with upregulation of FOXP3 expression in the peripheral blood.…”
Section: Statinsmentioning
confidence: 99%
“…Another potentially important strategy to limit MIRS may be the use of statins, as they have been rendered as potent cardioprotectors that have an interesting effect on T-cell activation [105]. For instance, rosuvastatin has been shown to limit MIRS through Treg expansion in a murine model [106], but the effect may not be exclusive to animal models, as a meta-analysis performed by Sorathia et al shows a vast increase in Tregs in patients that use rosuvastatin [107] ( Figure 3) (Table 1).…”
Section: Immunoregulation As a Modern Alternative To Immunosuppressionmentioning
confidence: 99%
“…Atorvastatin treatment of human peripheral blood mononuclear cells (PBMCs) increased the number of CD4 + CD25+Foxp3 + Treg cells 137 . By increasing the proportion of Treg cells and decreasing Teff cells, statins may reduce rejection and have direct anti‐atherogenic activity 138‐140 …”
Section: Dyslipidemiamentioning
confidence: 99%
“…128 However, in a 2-year extension study, a statistically significant difference in MACE was seen in the fluvastatin group without an observed difference in overall mortality or graft loss. 129 [138][139][140] Ezetimibe inhibits the absorption of cholesterol at the jejunal enterocyte brush border and is effective at lowering LDL in both adults and children. 141,142 A small study in pediatric kidney transplant recipients using ezetimibe in combination therapy with statins showed a notable decrease in LDL, total cholesterol, and triglycerides with no change in calcineurin inhibitor trough levels or allograft function.…”
Section: Scope and Backgroundmentioning
confidence: 99%